Analisis Kritis Eksistensi dan Urgensi Asbab An-Nuzul Dalam Penafsiran dan Istinbath Hukum - Arsal Arsal; Muhammad Zubir (Jurnal Ulunnuha, 2021)
This study aims to reveal the existence and urgency of asbab an-nuzul from the verses of the Qur'an in terms of interpreting and finding  the legal content. This research stands  by the pros and cons among scholars when addressing the existence of asbab an-nuzul al-Qur'an. The majority of scholar’s opinion said that  asbab an-nuzul which based on narration is very important  for  understanding  the content of the verse, but another scholar  come with the opposite opinion. There is an opinion says that asbab an-nuzul is not really important and seems it’s like a made up business. This research is critical analysis includes library research. While the method of  collecting  data analysis technique used is  inductive and comparative methods. The results of this study include: 1). The existence and urgency of asbab an-nuzul verses of the Qur'an are basicly important it can help to understand legal verses, but they are still casuistic not generalistic, there is a dictum al-Ibrah bi 'umum lafazh la bi khushushi sabab. 2). The Paradigm of the concept of asbab an-nuzul should be understood as a social setting (muqtadha al-hal) when the verses of the Qur'an were revealed to the Prophet SAW, with the term asbab an-nuzul macro, not only based on narration.